VITALIZING DIFFERENCES: LEGITIMIZING TO INCLUDE - Geraldo, Juliana Varela (Seven Editora, 2026)
Analyzing a scenario of oppression against subjectivities that deviate from what is referenced in a historically and socially established logic of mental institutions, patriarchal and racial structures, the following lines seek to map the mechanisms of this culture rooted in exclusion and individualization as a mode of biopolitical domination, as well as to map resistances and generate clues and proposals that create openings and promote inclusion, both with equitable access and with referential and representative centrality for those who are delegitimized and marginalized. Therefore, we have chosen the field of education as one of the most fruitful for cultivating and sowing, focusing on the concept of vitalizing life in its multiplicity of expressions; that is, appropriating living, existing, and relating as a masterpiece, breaking with the influences and interferences of moralizing currents, crafting and unveiling potentials for composition and transversalization of each singularity and event, integrating knowledge and cultures, ecology and subjectivity.